Endocrine Dysregulation and Functional Ovarian Cyst: A Case from Adolescent Gynecology - Khalid, Tabinda; Naqvi, Rubaba Abid; Haq, Aqsa Ikram Ul; Bashir, Shama (Journal of Rawalpindi Medical College, 2026)
Functional ovarian cysts are common in reproductive-age women, but their occurrence secondary to hypothyroidism is rare. We report a case of a 21-year-old female with poorly controlled hypothyroidism who presented with bilateral multiloculated ovarian cysts mimicking neoplastic pathology. Emergency laparotomy was performed due to worsening symptoms, and bilateral cystectomy with ovarian conservation was achieved. Histopathology confirmed corpus luteal cysts. Postoperative thyroid hormone replacement led to normalization of menstrual cycles and resolution of cysts. This case highlights the importance of thyroid evaluation in young women with ovarian masses to avoid unnecessary surgery and preserve fertility. Keywords: Ovarian Cysts, Corpus Luteum, Hypothyroidism, Thyroid Hormones/therapeutic use, Adolescent, Young Adult, Gynecology, Fertility Preservation.